Analisis distribusi kebutuhan pangan pokok hasil pertanian di Kota Mataram - Ahmad Suriadi; Sukmawati Sukmawati (Jurnal Agrotek Ummat, 2023)
The aim of this research is to find out the staple food distribution channels and to analyze the market diversity of each distribution channel. Primary data obtained through observation and interviews using a list of questions (questionnaire). Determination of respondents with purposive sampling method. From the results of the study, it was found that the distribution of staple food in the city of Mataram, namely where the commodity of rice circulating in the city of Mataram, there are two routes. Commodities Corn has one channel, Soybean has two channels, Shallots has one channel, Garlic has two channels, Big Red Chili, Curly Chili and Cayenne Pepper, has the same distribution channel, namely two channels.